Training on Developing Basic Service Media by Using Quizizz Media for Guidance and Counseling Teachers at Junior High Schools in Palembang City - Rozzaqyah, Fadhlina; Tanjung, Romi Fajar; Sucipto, Sigit Dwi; Qarsela, Qarsela; Destiana, Ririn; Akbar, Rizky Al (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
The guidance and counseling teacher or counselor's adjustment to technological developments is something that is absolutely necessary to balance the development of lifestyles, especially the current education system, so that they are not further left behind by developed countries. This activity aims to identify the skills of guidance counselors/counselors in providing technology-based counseling services and improve the skills of guidance counselors/counselors so that they can provide optimal guidance and counseling services based on technology. The target of the activity is Palembang City Middle School Counselor/BK Teachers, the number of participants is 25 people. To measure the increase in participants' skills in this activity, participants' knowledge evaluation instruments were used. Data analysis using the Excel application. Training on the use of the Quizizz application for BK teachers succeeded in increasing their understanding and skills in compiling interactive basic service media. The evaluation showed that participants were able to apply the training material effectively, from creating an account to implementing media in BK services. The results of this research show that the use of technology, such as Quizizz, can increase creativity, effectiveness and innovation in guidance and counseling services at schools.